Exploring the Relationship between Teachers’ Socio-economic Status and Their Teaching Profession Attitude at Secondary School Leve - Tanveer Iqbal Mughal, Mushtaq-ur-Rehman Siddiqui (PJE, 2024)
The main focus of this study was to find out the relationship between teachers’ socio-economic status (SES) and their teaching profession attitude at secondary school level in the province of Punjab. After extensive literature review and focus group discussion, four subcomponents of teachers’ SES have been selected named as qualification, income, occupational respect, wealth and while teaching values, attributes, salaries & incentives, and satisfaction with teaching profession were selected as sub-components of teaching profession attitude.